The biochemical changes caused by metolachlor and atrazine on wheat ( Triticum aestivum L.) varieties - Canakci, Songul; Karabulut, Fadime (Progress in Nutrition, 2020)
Summary. Aim: In this study, different concentrations (0, 100 μM, 300 μM, and 1000 μM) of Atrazine and Metolachlor were applied on 15-day-old bread wheat seedlings (of three varieties named as Bayraktar cv., İkizce cv. and Tosunbey cv. of Triticum aestivum L.) for 48 hours and their biochemical effects were investigated. Methods: In all the treatments on the seedlings, the hydroponic method was preferred. Results: In the leaves of atrazine-treated wheat seedling, GSH/GSSG ratio also increased in three varieties and MDA amount increased in Bayraktar and Tosunbey compared to the control. SOD activity increased in Tosunbey, decreased in İkizce and it firstly increased and then decreased in Bayraktar. CAT activity decreased in all three of the varieties. In the leaves of metolachlor-treated wheat seedlings, GSH/GSSG ratio decreased in three varieties and MDA amount increased in İkizce and Tosunbey, compared to the control. SOD activity decreased in Bayraktar, increased in İkizce and Tosunbey; and CAT activity decreased in all three varieties. Conclusion: In general, Atrazine was found to be more inhibitive compared to Metolachlor. In other words, Atrazine became more effective in causing oxidative stress in wheat seedlings.